The influence of entrepreneurial leadership and sustainability leadership on high-performing school leaders: Mediated by empowerment - Norhisham Mohd Kasim (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
The fifth shift of the Malaysian Education Blueprint (MEB) 2013-2015, stated that the ministry will ensure high-performing school leaders are placed in every school. But the main challenge for the Malaysian school leader is to improve and achieve the key performance indicators of high-performing schools. This study supports the aspirations of MEB 2013-2015 by identifying the best practices of leadership to achieve outstanding student performance as well as to maintain the high-performance of schools. Therefore, this study examines the influence of entrepreneurial leadership, sustainability leadership and empowerment towards high-performing school leaders in primary schools of East Coast Malaysia. The instrument used is a questionnaire adopted from several questionnaires developed by previous researches on entrepreneurial leadership, sustainable leadership, empowerment and high-performing school leaders. A total of 486 questionnaires were distributed to the respondents of 15 high-performing primary schools in Kelantan, Terengganu and Pahang using the random sampling technique. With a 58 percent return rate, the data were analyzed using SPSS version 24 and SmartPLS version 3.28 for descriptive analysis, measurement model and structural model. The findings show that variables such as entrepreneurial leadership exerted a significant influence on high-performing school leaders and sustainability leadership also exerted a significant influence on empowerment. In addition, the results of this study support the contributions of the study that have been proposed. The findings of this study will contribute to future research, particularly to researchers aiming to examine this leadership style in depth on school performance in Malaysia.
Keywords: 330; Empowerment; Entrepreneurial leadership; High-performing school leaders; Sustainability leadership